Acute Insulin Resistance Assessed by the Homeostatic Model Assessment in Acute Coronary Syndromes Without Previously Known Diabetes. (July 2014) - Lazzeri, Chiara; Valente, Serafina; Chiostri, Marco; Attanà, Paola; Mattesini, Alessio; Gensini, Gian Franco
We assessed the incidence and the prognostic role for early death of acute insulin resistance (by means of homeostatic model assessment [HOMA] index) in 1350 patients with acute coronary syndrome (ACS) consecutively admitted to our intensive cardiac care unit (ICCU). The incidence of HOMA positivity was 5% (68 of 1350), with the highest percentage of HOMA positivity among ST-segment elevation myocardial infarction (STEMI). Patients with HOMA positivity showed a higher body mass index ( P = .003), lower values of admission and discharge left-ventricular ejection fraction (LVEF; P < .001 and P = .003, respectively), and higher levels of peak troponin I (Tn I; P < .001). The HOMA index was an independent predictor of early death (odds ratio 1.724, 95% confidence interval 1.252-2.375, P = .001). In patients with ACS and without previously known diabetes, acute insulin resistance (HOMA index) is associated with a larger myocardial damage (ie, higher values of peak Tn I and lower LVEF) and a greater inflammatory activation (indicated by correlation with leukocyte count). The HOMA positivity was an independent predictor of in-ICCU mortality.